FREQUENCY OF DYSMENORRHOEA, ITS IMPACT AND MANAGEMENT STRATEGIES ADOPTED BY MEDICAL STUDENTS - Yasir, Saadia; Kant, Bushra; Dar, Muhammad Farooq (Journal of Ayub Medical College Abbottabad, 2014)
Background: Dysmenorrhea is quite frequent and may affect the daily activities especially during the early years of adolesence. This study aimed to evaluate the prevalence of dysmenorrhoea, its impact, and the management strategies adopted. Methods: This cross-sectional study was done with 356 consenting females studying at Mohiuddin Islamic University, Mirpur Azad Kashmir, between 18-25 years of age, with regular menstrual cycles and normal abdomino-pelvic ultrasound and not taking any medication. Information was gathered regarding age, residence, menstrual history, body mass index (BMI), associated symptoms, remedies used and days lost. Results: A total of 56.1% females had dysmenorrhoea. The mean age of participants was 21.01±1.54 years, mean age of menarche was 12.9±1.65 years, mean duration of menstrual flow was 4.75±1.27 days and mean BMI was 24.1±1.6. 17% of the participants were dieting and 26% had daily milk intake. 25% reported being absent due to pain and number of days lost was 1.5±1.0 days. Common symptoms associated with the dysmenorrhoea were difficulty concentrating in 65%, less involvement in social activities and sleep affected in 64%, mood disturbances in 58% and headache in 56%. Household remedies for dysmenorrhea were used by 43% and 66% used analgesics and only 4% sought medical advice for pain. Conclusion: Dysmenorrhoea is a very common problem affecting academic performance and limiting daily activities requiring appropriate intervention. <span style="font-size: 10.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Keywords:<span style="font-size: 10.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB"> Dysmenorrhoea, Body mass index, medical students <!–[if !supportLists]–>1. <!–[endif]–>Latthe PM, Champaneria R, Khan KS. Dysmenorrhoea. ClinEvid (Online). 2011;2011. pii: 0813. PubMed PMID: 21718556 <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>2. <!–[endif]–>Harlow SD, Campbell OM. Epidemiology of menstrual disorders in developing countries: a systematic review. BJOG. 2004;111:6-16. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 12.8pt; text-align: justify; text-indent: -12.8pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>3. <!–[endif]–>French L. Dysmenorrhea. Am Fam Physician 2005;71:285-91. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>4. <!–[endif]–>Ortiz MI. Primary dysmenorrhea among Mexican university students: prevalence, impact and treatment. Eur J Obstet Gynecol Reprod Biol 2010;152:73-7. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>5. <!–[endif]–>Okusanya BO, Garba KK, Okome GB, Ohiosimuan O. Menstrual pain and associated factors amongst undergraduates of Ambrose Alli University Ekpoma, Edo State, Nigeria. Niger J Med 2009;18:409-12. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>6. <!–[endif]–>Chia CF, Lai JH, Cheung PK, Kwong LT, Lau FP, Leung KH, et al. Dysmenorrhoea among Hong Kong university students: prevalence, impact, and management. Hong Kong Med J 2013;19:222-8. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>7. <!–[endif]–>Polat A, Celik H, Gurates B, Kaya D, Nalbant M, Kavak E, et al. Prevalence of primary dysmenorrhea in young adult female university students. Arch Gynecol Obstet 2009;279:527-32. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>8. <!–[endif]–>Cheng HF, Lin YH. Selection and efficacy of self-management strategies for dysmenorrhea in young Taiwanese women. J Clin Nurs 2011;20:1018-25. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>9. <!–[endif]–>Sugumar R, Krishnaiah V, Channaveera GS, Mruthyunjaya S. Comparison of the pattern, efficacy, and tolerability of self-medicated drugs in primary dysmenorrhea: A questionnaire based survey. Indian J Pharmacol 2013;45:180-3. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>10.<!–[endif]–>Campbell M, McGrath P. Use of medication by adolescents for the management of menstrual discomfort. Arch Pediatr Adolesc Med 1997;151:905-13. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>11.<!–[endif]–>Larroy C. Comparing visual-analog and numeric scales for assessing menstrual pain. Behav Med 2002;27:179-81. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 12.95pt; text-align: justify; text-indent: -12.95pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>12.<!–[endif]–>Unsal A, Ayranci U, Tozun M, Arslan G, Calik E. Prevalence of dysmenorrhea and its effect on quality of life among a group of female university students. Ups J Med Sci 2010;115:138-45. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>13.<!–[endif]–>Hirata M, Kumabe K, Inoue Y. Relationship between the frequency of menstrual pain and bodyweight in female adolescents. Nihon Koshu Eisei Zasshi 2002;49:516-24. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>14.<!–[endif]–>Montero P, Bernis C, Fernandez V, Castro S. Influence of body mass index and slimming habits on menstrual pain and cycle irregularity. J Biosoc Sci 1996;28:315-23. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>15.<!–[endif]–>Abdul-Razzak KK, Ayoub NM, Abu-Taleb AA, Obeidat BA. Influence of dietary intake of dairy products on dysmenorrhea. J Obstet Gynaecol Res 2010;36:377-83. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>16.<!–[endif]–>Obeidat BA, Alchalabi HA, Abdul-Razzak KK, Al-Farras MI. Premenstrual symptoms in dysmenorrheic college students: prevalence and relation to vitamin D and parathyroid hormone levels. Int J Environ Res Public Health 2012;9:4210-22. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>17.<!–[endif]–>Rodrigues AC, Gala S, Neves A, Pinto C, Meirelles C, Frutuoso C, VÃtor ME. Dysmenorrhea in adolescents and young adults: prevalence, related factors and limitations in daily living. Acta Med Port 2011;24:383-8. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>18.<!–[endif]–>O’Connell K, Davis AR, Westhoff C. Self-treatment patterns among adolescent girls with dysmenorrhea. J Pediatr Adolesc Gynecol 2006;19:285-9. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>19.<!–[endif]–>Ma YX, Ye XN, Liu CZ, Cai PY, Li ZF, Du DQ, et al. A clinical trial of acupuncture about time-varying treatment and points selection in primary dysmenorrhea. J Ethnopharmacol 2013;148:498-504. <p class="MsoListParagraph" style="margin-top: 0in; margin-right: 0in; margin-bottom: .0001pt; margin-left: 13.1pt; text-align: justify; text-indent: -13.1pt; mso-char-indent-count: -1.64; line-height: normal; mso-list: l0 level1 lfo1;"><!–[if !supportLists]–>20.<!–[endif]–>Chaudhuri A, Singh A. How do school girls deal with dysmenorrhoea? J Indian Med Assoc. 2012;110:287-91. Chan SS, Yiu KW, Yuen PM, Sahota DS, Chung TK. Menstrual problems and health-seeking behaviour in Hong Kong Chinese girls. Hong Kong Med J. 2009;15:18-23